THE PENGARUH PERSONAL SELLING AGEN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN NASABAH ASURANSI SUN LIFE FINANCIAL SINGARAJA - Ni Luh Wayan Sayang Telagawathi Telagawathi; Ni Nyoman Yulianthini (Fakultas Ekonomi Dan Bisnis Universitas Palangka Raya (UPR), 2022)
This research aims to examine the cause of (1) personal selling agent and product quality toward purchasing decision, (2) personal selling toward purchasing decision, (3) product quality toward purchasing decisions empirically. The design of this research is causal quantitative research design. One of the methods of data collection is questionnaire, which is analyzed by using multiple regression with classical assumption test. The result of the research shows that there are significant influence from (1) personal selling and product quality toward purchasing decision with contribution influence of 0,785 (2) personal selling toward purchasing decision with contribution influence of 0,445 and (3) product quality toward purchasing decision with contribution influence of 0,173 to the client of PT. Sun Life Financial